MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS PADA ANAK USIA DINI DENGAN MENGGUNAKAN MEDIA PUZZLE ANGKA - Khoirussifa Sholihah (IKIP Siliwangi, 2018)
In the context of logical thinking the child will know about classifying objects based on function, shape or color or size, recognize patterns of ab-ab / abc-abc and repeat them. Increasing the ability to think logically with the puzzle media mental children will also be accustomed to being calm, diligent and patient in getting things done. So this research focuses on the implementation of the use of puzzle media in learning logical thinking in RA Nurul Yusro with the research title